Information Overload in a First-price Auction - Greve, T. (New York University (NYU), 2020)
This paper studies a first-price auction in a procurement setting, where each bidder is requested to submit both a cost to be compensated for when delivering the project and an amount of information about the project, obtained via a questionnaire. The questionnaire can be of different levels of complexity. The bidders are interested in shading their bids. However, they will also respond in accordance to the complexity of the questionnaire. The more complex the questionnaire, the greater the effort the bidders have to use to ensure consistency within the information to be delivered as well as between the information and the proposed compensation. We show that the introduction of complexity leads to the possibility of multiple equilibria and, under suitable assumptions, to a unique equilibrium, where bidders submit truthful bids.